In silico Investigations of the Mode of Action of Novel Colchicine Derivatives Targeting β-Tubulin Isotypes: A Search for a Selective and Specific β-III Tubulin Ligand - Pallante, Lorenzo; Rocca, Antonio; Klejborowska, Greta; Huczynski, Adam; Grasso, Gianvito; Tuszynski, Jack A.; Deriu, Marco A. (Frontiers in Chemistry, 2020)
The cardinal role of microtubules in cell mitosis makes them interesting drug targets for many pharmacological treatments, including those against cancer. Moreover, the different expression pattern of several tubulin isotypes represents a great opportunity to improve the selectivity and specificity of the employed drugs and to design novel compounds with higher activity only on interested cells. In this context, isotype βIII represents an excellent target for anti-tumoral therapies since it is overexpressed in most cancer cells and correlated with drug resistance. Colchicine is a well-known antimitotic agent, which is able to bind the tubulin dimer and to halt the mitotic process; however, it shows high toxicity also on healthy cells and it is not specific for isotype βIII. In this context, the search for colchicine derivatives is mater of great attention in cancer research. In this study, homology modelling techniques, molecular docking, and molecular dynamics simulations have been employed to characterize the interaction between 55 promising colchicine derivatives and tubulin isotype βIII. In a greater detail the considered compounds were screened and ranked based on their binding affinity and conformational stability in the colchicine binding site of tubulin βIII. Results from this study point the attention on an amide of 4-chlorinethiocolchicine. This colchicine-derivative is characterized by a unique mode of interaction with respect to all other compounds considered in the study which is primarily characterized by the involvement of the α-T5 loop, key player in microtubule longitudinal interdimer interactions. Information coming from the present study may be important in the design process of colchicine-derivatives targeting drug resistant cancer phenotypes.